Analisis Roadmap Pengembangan Industri Jagung di Provinsi Gorontalo - Djamila Podungge; Imam Mashudi; Andi Yusuf Katili (Universitas Muhammadiyah Gorontalo, 2019)
This research aims to: (1) The corn industry development roadmap in Gorontalo Province, (2) Supporting and inhibiting factors of the corn industry development in Gorontalo Province. This research uses a qualitative approach with data collection techniques is an interview. The results of this research are: 1) Gorontalo Province have the corn industry development roadmap which refers to the implementation of agribusiness as a whole and integrated starting from the operational policy, strategy, program, and its activities but its implementation is still not optimal; 2) Factors supporting the development of the Corn Industry in Gorontalo Province consists of provincial government policies, have an Image with a Brand “Jagung” and have the facilities to do export-scale marketing; and 3) Inhibiting factors in the development of the corn industry in Gorontalo Province among others: the ability of farmers to process corn products, unfair market price competition, and capital is still small at the level of IKM Penelitian ini bertujuan untuk mengetahui 1) Roadmap Pengembangan Industri Jagung di Provinsi Gorontalo dan 2) Faktor Pendukung dan Penghambat Pengembangan Industri Jagung di Provinsi Gorontalo. Penelitian ini menggunakan Pendekatan Kualitatif dengan teknik pengumpulan Datanya adalah Wawancara. Adapun hasil penelitian ini adalah: 1) Provinsi Gorontalo telah memiliki Roadmap Pengembangan Industri Jagung yang mengacu pada pelaksanaan agribisnis secara utuh dan terpadu mulai dari kebijakan operasionalnya, strategi, programnya dan kegiatannya akan tetapi implementasinya masih belum maksimal; 2) Faktor pendukung pengembangan Industri Jagung di Provinsi Gorontalo terdiri dari adanya kebijakan Pemprov, Miliki Citra dengan Brand “Jagung”, serta Memiliki sarana untuk melakukan pemasaran skala ekspor; dan 3) Faktor Penghambat pengembangan industry jagung di provinsi Gorontalo antara lain: kemampuan petani untuk mengolah hasil jagung, persaingan harga pasar yang tidak sehat dan Modal yang masih kecil di tataran IKM.